THE IMPROVEMENT OF THE CURSIVE HANDWRITING SKILL THROUGH EXPLICIT INSTRUCTION MODEL (A Classroom Action Research of the Second Grade Students of State Primary School Soropadan No. 180 Surakarta in Academic Year 2017/2018) - Linda Fitrianti; Sadiman Sadiman; Matsuri Matsuri (Universitas Sebelas Maret, 2018)
The objective of this research is to improve the cursive handwriting skill through Explicit Instruction model of the second grade students. The type of this research was Classroom Action Research conducted two cycles. Each cycle consisted of four phases, namely: planning, acting, observing, and reflecting. The subjects of this research are teacher and second grade students which amounted to 31 students. The data of this research were collected by observation, interview, test, and documentation. The data of this research were validated by using data source and technique triangulations. The data were analyzed by using the interactive analysis model. Based of the research, seen from minimum passing score 70, the classical passing score of students writing skill was increased, from 29% in pre-action, increased to 61% in cycle I, and increased to 84% in cycle II. This research can be concluded that through Explicit Instruction model can improve cursive handwriting skill of the second grade students of State Primary School Soropadan No. 108 in academic year 2017/2018.